The gilded age [compact disc, unabridged] - Twain, Mark, 1835-1910; Warner, Charles Dudley, 1829-1900 (Blackstone Audio, 2011)
Despite owning a large swath of undeveloped land, Silas Hawkins and his Tennessee family live in poverty in the 1870s. Before he can get rich from the sale of his property, Si dies. However, his adoptive daughter, Laura, travels to Washington, D.C. in an effort to sell the land to the federal government. Meanwhile, Philip Sterling and Henry Brierly also seek to sell off their land, albeit in different ways.